Chemical Composition and Biological Activities of the Leaf Essential Oils of Curcuma longa, Curcuma aromatica and Curcuma angustifolia - Jawaher J. Albaqami; Hamida Hamdi; Arunaksharan Narayanankutty; Naduvilthara U. Visakh; Anju Sasidharan; Aswathi Moothakoottil Kuttithodi; Ademola C. Famurewa; Berin Pathrose (MDPI AG, 2022)
Curcuma species are widely used as a food additive and also in various medicinal purposes. The plant is a rich source of essential oil and is predominantly extracted from the rhizomes. On the other hand, the leaves of the plants are usually considered as an agrowaste. The valorization of these Curcuma leaf wastes into essential oils is becoming accepted globally. In the present study, we aim to extract essential oils from the leaves of Curcuma longa (LEO), C. aromatica (REO), and C. anguistifolia (NEO). The chemical composition of these essential oils was analyzed by GC-MS. Free radical scavenging properties were evaluated against the radical sources, including DPPH, ABTS, and hydrogen peroxide. The antibacterial activity was assessed by the disc diffusion method and Minimum inhibitory concentration analysis against Gram positive (Staphylococcus aureus) and Gram negative (Escherichia coli, Pseudomonas aeruginosa and Salmonella enterica) bacteria. Results identified the compounds α-phellandrene, 2-carene, and eucalyptol as predominant in LEO. The REO was predominated by camphor, 2-bornanone, and curdione. The main components detected in NEO were eucalyptol, curzerenone, α-lemenone, longiverbenone, and α-curcumene. Antioxidant properties were higher in the LEO with IC50 values of 8.62 ± 0.18, 9.21 ± 0.29, and 4.35 ± 0.16 μg/mL, against DPPH, ABTS, and hydrogen peroxide radicals. The cytotoxic activity was also evident against breast cancer cell lines MCF-7 and MDA-MB-231 cells; the LEO was found to be the most active against these two cell lines (IC50 values of 40.74 ± 2.19 and 45.17 ± 2.36 μg/mL). Likewise, the results indicated a higher antibacterial activity for Curcuma longa essential oil with respective IC50 values (20.6 ± 0.3, 22.2 ± 0.3, 20.4 ± 0.2, and 17.6 ± 0.2 mm). Hence, the present study confirms the possible utility of leaf agrowastes of different Curcuma spp. as a possible source of essential oils with pharmacological potential.